Mujeres viajeras y escritura (es)trábica en y desde la Argentina: Lina Beck Bernard, Laura Pariani y Cecilia Prenz (El Hilo de la Fabula, 2022)
The aim of this article is to analyze the production of three migrant women writers. Two of them are European but from different periods: Lina Beck Bernard (mid-19th century) and Laura Pariani (second half of the 20th century); and the third one is an Argentinian living in Europe: Cecilia Prenz (between centuries). In their journeys to and from Argentina, the three women experienced the contact between worlds in a personal way, generating in their fictionalizations and autobiographical texts a particular strabismic gaze (Crolla, 2008-2014). To this end, it is proposed to widen the categories of "migrant speech" and "migrant writers" in order to reflect upon the way in which a writing space considered as “other” can be conquered by women by crossing borders through their gaze, their reading and their speech. And where physical movement and physical contact with "the other" determines highly significant political, aesthetic and linguistic positions in their own discursive movements.
Keywords: Migrant women; Lina Beck Bernard; Laura Pariani; Cecilia Prenz